STRATEGI INDONESIA MEWUJUDKAN ASEAN OUTLOOK ON INDO-PACIFIC (AOIP) UNTUK MENCIPTAKAN STABILITAS DI KAWASAN INDO-PASIFIK - Langgeng Gilang Pangestu (2020)
Today a new region is forming, the Indo-Pacific which is based on a variety of potential within. This environment creates colliding interests of various countries. Rivalry between China and the United States is inevitable, the impact of which is on regional stability. Indonesia, which is right in the heart of the Indo-Pacific, faces various threats, national interests, regional stability and ASEAN centrality. This paper uses the concepts of national interest, strategic environment, security community, and diplomacy with a descriptive qualitative research approach (literature study and interviews) that describes the research problem empirically. The results of the study describe the process from the creation of the ASEAN Outlook on Indo Pacific (AOIP) to being approved by ASEAN. Keywords: Indo-Pacific, Indonesia, ASEAN, diplomacy